Impact of Reddit Retail Investors - HERMANN, JONA GABRIEL (2022)
In this thesis we examine the impact the amount of comments on the social media platform Reddit has on the development of stocks from Microvision Inc., Clover Health Investments Corp. and Bed Bath & Beyond Inc. Thereby we focus on the subreddit wallstreetbets and model the impact of comments which include the respective stock symbol have on the stock price volatility. To account for retail investor interest besides Reddit and general market trends we include further variables in our model. We then test whether a specific event has triggered the rise in comments and examine how the rise in comments influenced further indicators such as short interest and stock price. Lastly, we analyse the findings in the context of literature findings and theoretical assumptions. We identify a relation between the amount of Reddit comments and the stock price volatility. Furthermore, we show that Reddit retail investors have an impact on other factors such as stock price and short interest. Although those findings are more mixed and not as straightforward as the findings regarding the stock price volatility. We find that our findings are consistent with prior works about retail investor behaviour and herding behaviour. Our findings contribute to the literature about retail investors behaviour and their increasing impact on the stock market. Therefore our research offers interesting insights for policy makers, market regulators and other market participants.